FRAKSINASI DAN IDENTIFIKASI SENYAWA TANIN PADA DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Elok Kamilah Hayati; A. Ghanaim Fasyah; Lailis Sa’adah (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
Fractionation of tannic compound from star fruit leaves was conducted by maseration using acetone : water(7:3), and analytical and preparative thin layer chromatography using a variety of eluents. The isolates obtained wereidentified using UV-Vis and FT-IR Spectrophotometer.The best eluent for both analytical and preparative TLC was found to be n-butanol : water : acetic acid(4:1:5), which gave three isolates with Rf of 0.53, 0.61, and 0.68. The second isolate (Rf = 0.61), showed a maximumabsorption at 331 nm on the UV-Vis spectra. Its IR spectra showed specific absorptions such as OH-assymetricstretch (3372.2 cm-1), aromatic overtone (2071.8 cm-1), and aromatic and benzene stretches at 1625.8 cm-1 and 782.5cm-1 respectively. These spectra suggest that the tannic compound was either flavan pent-3,6,7,4',5'-ol or flavanpent-3,7,8,4',5'-ol.